Nutritional Value of Nannochloropsis oceanica for Weaner Piglets - Andreia A. M. Chaves; David M. Ribeiro; Cátia F. Martins; Tatiane Fernandes; Margarida R. G. Maia; António J. M. Fonseca; Ana R. J. Cabrita; Susana P. Alves; Mário Pinho; Rui J. B. Bessa; André M. de Almeida; João P. B. Freire (Animals)
This study evaluates the nutritional value of spray-dried Nannochloropsis oceanica biomass to infer its applicability for weaner piglet feeding. Twenty-four piglets were randomly allocated to four dietary treatments (n = 6) with increasing N. oceanica inclusion (0, 5, 10, and 15%) levels. After a 4-day adaptation period, the digestibility experiment lasted two weeks, with daily excreta collection. Total tract apparent digestibility (TTAD), N balance, intestinal pH, histomorphology, and volatile fatty acid (VFA) concentrations were measured. No significant differences were observed in feed intake, growth, or intestinal morphology (p > 0.05). N intake increased linearly (p = 0.005) with N. oceanica inclusion, while N retention efficiency remained unchanged (p = 0.058). VFA concentrations decreased linearly (p < 0.001). The TTAD of dry matter (DM), organic matter, ether extract, and gross energy decreased (p < 0.05) with higher N. oceanica levels, while the ash TTAD increased (p < 0.001). The estimated TTAD values for N. oceanica biomass were 72.5% for DM, 82.9% for N, and 64.4% for gross energy. The digestible energy, metabolisable energy, and digestible crude protein values estimated for N. oceanica were 12.74 MJ/kg DM, 12.40 MJ/kg DM, and 20.4% DM, respectively. This information enabled the first nutritional characterisation of N. oceanica for weaner piglets, ultimately leveraging its use in piglet diet formulation.